Small-specimen testing, with image-based analysis, for crack propagation resistance in polygranular nuclear graphite - Marrow, J; Scotson, D; Jin, X; Chen, H; Chen, Y; Koko, A; Earp, P; Wu, H (ASTM International, 2022)
To enable monitoring of graphite that has been exposed to irradiated, high- temperature environments, there is a need for analysis methods that are suitable for fracture toughness measurements in small test specimens. Quasistatic fracture propagation has been studied for two candidate graphites for next-generation nuclear energy, SNG742 and T220, using small specimens in the double-cleavage drilled-compression (DCDC) geometry (20 × 7 × 7 mm). Com- pression of the DCDC specimen initiated stable crack propagation, and the surface full-field displacements were measured by digital image correlation. A phase congruency method was applied to the displacement field to quantify the crack lengths, crack opening displacements, and crack tip opening angles. The classical analytical solution for the stress intensity factor in the DCDC specimen gave unrealistic results due to its boundary condition assumptions. A new analysis method is proposed in which the measured crack displacement field is injected as boundary conditions into a finite element model, allowing the J-integral to be evaluated via the contour integral method, which then provides the mode 1 stress intensity factor during quasistatic crack propagation. With the assumption of linear elasticity, the critical stress intensity factor in T220 was constant for crack propagation up to 6 mm and lower than that in SNG742, which showed rising fracture resistance for longer cracks. The analysis was validated using Macor, a linear elastic fine-grained glass ceramic with known fracture toughness without significant R-curve behavior. The small-specimen graphite results are consistent with the reported fracture toughness from large-specimen tests, but the values are overestimations due to the nonlinear behavior of unirradiated graphite. Methods to extract nonlinear elastic properties by inverse analysis are discussed. The outlook for fracture testing of irradiated graphite at elevated temperatures is considered.